Anti Proliferative Potentials of Quail Eggs and Aqueous Root Extract of Cymbopogon citratus on Radicle Length of Fast Growing Sorghum bicolor Seeds - Arome, D (International Journal of Pharmaceutical & Biological Archive, 2013)
Anti Proliferative Potentials of Quail Eggs and Aqueous Root Extract of Cymbopogon citratus on Radicle Length of Fast Growing Sorghum bicolor Seeds